Analisis Daya Saing dan Dampak Kebijakan Pemerintah pada Usahatani Bawang Merah di Kabupaten Buton - Sitti Rahmah Saraswati; Marsuki Iswandi; La Ode Alwi (Universitas Halu Oleo, 2022)
This study aims to analyze the competitiveness of shallot farming in South Buton Regency and the impact of government policies on that competitiveness. The research sample is 73 people. Data analysis using the Policy Analysis Matrix (PAM) shows that shallot farming in South Buton Regency has competitiveness in terms of competitiveness. from the aspect of competitive and comparative advantage with PCR and DRCR values less than one. This is in line with the level of private and social benefits of farming which has a positive value. The impact of government policies on the output side causes the actual price of shallot production in the local market to be higher than the price in the national market. The impact of government policies on the input side causes shallot farmers in South Buton Regency to pay tradable input costs, namely inorganic fertilizers, which are higher than the social price. However, the seed subsidy policy has provided a positive surplus for the income of shallot farmers. Simultaneously, input and output policies can provide positive incentives for farmers and support the development of shallot farming in South Buton Regency Keywords: shallot; Policy Analysis Matrix; competitive advantage, comparative advantage